Membangun Iklim Institusi Pendidikan Islam Yang Berorientasi Etos Kerja - Mustajab Mustajab (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: This paper examines the efforts to be made to build a climate of educational institutions of Islamic-oriented work ethic. The results showed that the performance of an organization is determined by the mood of the work environment in the organization. Similarly, the performance is determined by the educational institution or the atmosphere of the workplace climate at the institution. In developed countries, research on school climate at work has been developed with well-established and significant contribution to the establishment of effective institutions. Keywords: climate, institutions, Islamic education, work ethic.